Livro-reportagem: cinco atletas paralímpicos e suas histórias de vida - Montenegro, Sérgio Paiva (2017)
Considering that Parasport is a subject of great relevance, however, little explored and publicized in the communication vehicles and academic environment, this work aims to produce a book-report on athletes from Paraíba who competed in Rio 2016 Paralympics, showing how they started their activities in parasport, their life history, the prejudices suffered, the difficulties due to the deficiency in order to compete, as well as the participation and experience during the games. For the production of this book, the privileged resource was to conduct interviews with five athletes from Paraíba, using as main criterion of choice the fact of residing in the state of Paraiba. The objective of this study is to awaken society by its importance and respect for people with disabilities. The report, in its development, involves a contextual panorama of parasport in the world, in Brazil and Paraíba, it also presents a discussion on social inclusion and legal devices and bases the strategies adopted as: in-depth interview, construction of book-report, addressing the discussions on literary journalism and profiles.